PERANCANGAN BENCH MULTIFUNGSI BERGAYA JAPANDI - Damayanti, Friska; Setiawan, Ade (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2025)
Land limitations have increased the trend of limited housing development, based on this, it is necessary to choose the right furniture to support residential activities, one solution is to choose multifunctional furniture. Bench is furniture that is usually used only as a seat, in an era of high interest in multifunctional furniture and design trends that continue to grow, one of which is the Japandi style, a study was conducted that aims to create multifunctional Japandi furniture that combines Japanese minimalist aesthetics and Scandinavian practicality, so that it can optimize limited residential space. This study examines the elements of Japandi design which include the use of natural materials, neutral color palettes, and simple shapes. The multifunctional bench that was designed not only functions as a seat, but is also equipped with storage facilities to increase functionality without sacrificing aesthetic value. The research method uses a quantitative approach by involving respondents in filling out questionnaires, and using the design thinking design method which in its stages starts from empathize, define, ideate, prototype to test. Based on the data that has been processed, this product received a rating of 97.5% (very satisfied) both in terms of function and aesthetics.